Pengaruh Metode Pengolahan Terhadap Aktivitas Antioksidan Dan Karakteristik Teh Herbal Daun Matoa (Pometia pinnata) - Liana Dewi, Putu; Ari Yusasrini, Ni Luh; Wisaniyasa, Ni Wayan (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 10 No 2 (2021): Jurnal ITEPA, 2021)
This study aims to determine the effect of processing methods on antioxidant activity and characteristics of matoa leaf herbal tea ( Pometia pinnata ) as well as to obtain the right processing method which produces matoa leaf herbal tea ( Pometia pinnata ) with the antioxidant activity and the best characteristics. The design used in this study was a Completely Randomized Design with the treatment of method processing consisting of 4 levels, method A (oven drying), method B (steaming and oven drying), method C (withening and roasting), and method D (steaming and roasting). This study was repeated 4 times to obtain 16 trial units. The data obtained were analyzed by analysis of variance and if the treatment had a significant effect it was followed by Duncan's test. The results showed that the processing method significantly affected the water content, crude fiber content, extract content in water, total flavonoids, total phenols, antioxidant activity, IC 50, the sensory characteristics include color, aroma, taste and overall acceptance, and color objectively, but the treatment method has no significant effect on the ash content. The matoa leaf herbal tea with method A (oven drying) had the highest antioxidant activity and the best sensory characteristics with a water content of 8.46%, ash content of 4.64%, crude fiber content of 53.17%, extract content in water 5.25%, total flavonoids 0.87mgQE/g, total phenols 17.35mgGAE/g, antioxidant activity 87.50%, IC 50 57.94ppm and color determination l , a , b (18.33: 12.02: 10.48) as well as yellowish color sensory characteristics, very typical aroma of matoa leaf herbal tea, taste rather bitter, and overall acceptance likes.